ANALISIS LOAN TO DEPOSIT RATIO (LDR) DAN CAPITAL ADEQUANCY RATIO (CAR) TERHADAP RENTABILITAS PADA PT. BANK TABUNGAN NEGARA (PERSERO) Tbk - Yuslinda Nasution (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2016)
This study aims to identify, analyze and be able to explain financial ratios, especially the level of liquidity that is calculated by using the ratio of loan to deposit ratio (LDR), calculating the solvency level by using the ratio of Capital Adequacy Ratio (CAR), and calculate profitability by using the ratio Retun On Assets (ROA), Return On Investment (ROI) and Net Interest Margin (NIM) In PT Bank Tabungan Negara (Persero) Tbk, which is one of the State Owned Enterprises in the field of banking services primarily in credit financing.To obtain the necessary data, the authors use data collection techniques, the type of data used in the form of primary data and secondary data.Based on the results of data processing by the author, it is known that there are three conclusions. The First. of the results of the liquidity ratio LDR decline in 2014 due to an increase of 1.66% higher than the savings credit, and an increase back in 2015 of 3.52% for loans greater than the savings. Second, the results of the solvency ratio increased in 2014 compared to 2013 of 2.66% is due to an increase of capital by the end of 2013. And a decline back in 2015 of 2.07% is due to the decline in capital activities over the previous year. Third, the results of Profitability ratios using ROA calculation decreased by 0.08% in 2014 and decreased by 0.09% return this happens because the increase in net income is followed by an increase in the number of significant assets annually. While using the ROE also decreased by 0.75% in 2014 and decreased by 0.12% return is due to the growth of the share capital. And calculations using the NIM in 2014 increased by 0.07% due to significant asset growth, but a decline back in 2015 by 0.29% due to an increase in interest rates as a result of the BI rate.Can be seen from the calculation of financial ratios and earnings at PT Bank Tabungan Negara (Persero) Tbk showed good conditions and positive, although LDR exceed the provisions of Bank Indonesia, is because BTN is a bank loan portfolio for the long term.